Importancia de la capacitación docente para la inclusión educativa, en la Unidad Educativa “Ramón Páez – Melchor de Benavides” ubicada en el barrio Patután, parroquia Eloy Alfaro, cantón latacunga, provincia de Cotopaxi en el año lectivo 2014-2015 - Remache Moreno, Tania Gabriela (2015)
This work focuses on the teachers’ training for educational inclusion in the "Ramón Páez- Melchor de Benavides” educational unit, creating within the teachers a pedagogical vision of imparting new knowledge, becoming the facilitator and mediator between the student and the teaching-learning process, for which the pedagogical research is directed primarily to the benefit of the students. For this, it is necessary to start with a brief account of the background and scientific foundation of inclusive education and its characteristics, in order to emphasize values and competences to be acquired and developed by a teacher in his or her teaching management, which is complementary to the ongoing and continuous training with the teacher to meet diverse educational needs. Finally, the proposal, a training didactic guide for Inclusive Education in Teachers in the educational unit "Ramón Páez- Melchor de Benavides", will be the main source of motivation for teachers, students and the social environment to promote academic achievement and the interrelation of the educational community in general, that will enable the students to acquire quality education and warmth.